ANALYSIS OF FACTORS INFLUENCING THE CONVERSION OF PADDY FIELDS (Oryza sativa) TO OIL PALM (Elaeis gueneensis Jacq) IN PADANG LAWAS REGENCY - Timbul Harahap; Siti Mardiana; Gustami Harahap (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Agriculture consists of various subsectors, including food crops and plantation crops, which differ in management systems and impacts. In recent years, the conversion of paddy fields into oil palm plantations has increased in several regions of Indonesia, indicating a shift from food-oriented agriculture to plantation-based agriculture that affects environmental conditions and rural livelihoods.This study aims to analyze the factors influencing the conversion of paddy fields into oil palm plantations in Central Barumun District, Padang Lawas Regency, and to compare paddy farmers’ income before and after land conversion. The study employed an interview-based survey of 27 farmers, with primary and secondary data analyzed using descriptive quantitative and qualitative methods. The results indicate that oil palm farm income significantly influences land conversion, while farmers’ age and farming experience do not. The average income increased from IDR 1,215,325 per hectare per month before conversion to IDR 1,690,852 per hectare per month after conversion